Characterisation of mechanical properties of 15-5PH stainless steel manufactured through direct energy deposition. (August 2022) - Tapoglou, Nikolaos; Clulow, Joseph; Patterson, Andrew; Curtis, David
Abstract: Manufacturing of components through additive manufacturing has become increasingly popular over the last years. Direct energy deposition (DED) is one of the methods gaining popularity due to the high throughput of the methods compared to powder bed fusion methods. For the establishment of DED as a viable option for manufacturing mission critical components, the material characteristics and the mechanical properties of the deposited material must be thoroughly understood. This research focuses on the investigation of the mechanical properties of 15-5PH stainless steel manufactured with direct energy deposition and the effect of heat treatment on the characteristics of the components that were manufactured. The effect of the orientation of the build relevant to the test orientation was examined with relevant tests while a benchmark against wrought 15-5PH was also examined. Finally, the characteristics of the bond between an AM coupon and a base material were investigated.